Nickel-rich layered positive electrode material, preparation method thereof and solid-state battery

Through the coordinated coordination of the nickel content gradient and the nitrogen-doped carbon coating, the structural instability problem of nickel-rich layered NCM positive electrode material under high temperature and high voltage is solved, and high stability and excellent electrochemical performance are achieved.

CN119725458APending Publication Date: 2025-03-28JINGMEN GEM NEW MATERIAL CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411913161.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing nickel-rich layered NCM positive electrode materials have unstable structures under high temperature and high voltage, resulting in the formation of nickel oxides and oxygen release, reducing rate performance, and side reactions with solid electrolytes, resulting in reduced capacity and deterioration of structure.

Method used

The structural stability and electrochemical properties of the cathode material are improved by reducing the gradient of the nickel content from the core to the shell and the coordinated cooperation of the nitrogen-doped carbon cladding. The carbon cladding enhances electron and ion conductivity, avoids direct contact between the active material and the electrolyte, and promotes the carbon layer to be firmly anchored on the surface of the nickel-rich matrix material.

Benefits of technology

The high stability of the positive electrode material during the circulation process is achieved, the magnification and circulation performance are improved, the cycle life is extended, and the overall performance of the solid-state battery is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725458A_ABST
    Figure CN119725458A_ABST
Patent Text Reader

Abstract

The invention provides a nickel-rich layered positive electrode material, a preparation method thereof and a solid-state battery. The nickel-rich layered positive electrode material comprises a nickel-rich base material and a nitrogen-doped carbon coating layer coating the surface of the nickel-rich base material, the nickel-rich matrix material comprises a nickel-cobalt-lithium layered oxide inner core and a nickel-cobalt-manganese-lithium layered oxide shell layer positioned on the surface of the nickel-cobalt inner core; the molar weight ratio of nickel in the nickel-cobalt-lithium layered oxide core is greater than that of nickel in the nickel-cobalt-manganese-lithium layered oxide shell layer. The positive electrode material provided by the invention is stable in structure and excellent in capacity, rate and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid-state batteries and relates to a nickel-rich layered positive electrode material and a preparation method thereof and a solid-state battery. Background Art

[0002] Lithium-ion batteries have been widely used in electric vehicles and hybrid vehicles due to their high efficiency and environmental protection. In order to develop lithium-ion batteries with lower cost, better safety performance and higher energy density, all-solid-state lithium-ion batteries (ASSLB) have become the focus of current research. All-solid-state lithium-ion batteries are mainly composed of positive electrode materials, negative electrode materials and solid electrolytes, among which the stability of the positive electrode material is the key factor determining the performance of lithium-ion batteries. Improving the stability of the positive electrode material is not only beneficial to its own capacity retention rate, but also reduces the volume change of the positive electrode material caused by repeated lithium insertion and extraction, which effectively avoids further contact loss and alleviates the space charge layer effect and the degradation of the solid electrolyte.

[0003] Among positive electrode materials, compared with cobalt-rich positive electrode materials (LiCoO2), nickel-rich layered NCM positive electrode materials are more competitive in the market due to their advantages of low cost, high capacity, high energy density, and high operating voltage. However, excessive nickel concentration at high temperature and high voltage will lead to unstable Ni 4+ NiO is formed and oxygen is released. The electrochemically inactive NiO layer increases the lithium ion diffusion barrier, further reducing the rate performance; and the released oxygen may cause serious side reactions with the solid electrolyte. In addition, the cation mixing and the insulating layer produced by the surface with air and moisture are the main reasons for the decrease in capacity and structural deterioration of the nickel-rich layered NCM positive electrode.

[0004] CN111653743A discloses an aluminum-coated nickel-cobalt-manganese ternary lithium battery positive electrode material, and its preparation method and application. Aluminum source as a surface coating agent can effectively inhibit the structural deterioration of the positive electrode material, but the poor electronic and ionic conductivity seriously affects the rate performance.

[0005] CN116525787A discloses a carbon-coated NCM622 ternary positive electrode material and a preparation method thereof. The conductive carbon coating layer can improve the electronic conductivity of the material and reduce the occurrence of side reactions, but the carbon coating layer is not in firm contact with the positive electrode material, making the carbon coating layer easy to peel off during a long cycle, reducing the rate capability and capacity retention capability.

[0006] Therefore, how to improve the structural stability of nickel-rich positive electrode materials and enhance their electrochemical performance is a technical problem that needs to be solved urgently. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention aims to provide a nickel-rich layered positive electrode material and a preparation method thereof and a solid-state battery. The positive electrode material provided by the present invention has a stable structure and excellent capacity, rate and cycle performance.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a nickel-rich layered positive electrode material, the nickel-rich layered positive electrode material comprising a nickel-rich base material and a nitrogen-doped carbon coating layer coated on the surface of the nickel-rich base material;

[0010] The nickel-rich matrix material includes a nickel-cobalt-lithium layered oxide core and a nickel-cobalt-manganese-lithium layered oxide shell located on the surface of the nickel-cobalt-lithium layered oxide core; the molar ratio of nickel in the nickel-cobalt-lithium layered oxide core is greater than the molar ratio of nickel in the nickel-cobalt-manganese-lithium layered oxide shell.

[0011] The nickel-rich layered positive electrode material provided by the present invention improves the stability of the positive electrode material during the cycle process through the gradient reduction of the nickel content from the inner core to the shell layer and the synergistic cooperation of the nitrogen-doped carbon coating layer; at the same time, the carbon coating layer can further enhance the electronic and ionic conductivity and more effectively avoid direct contact and reaction between the active material and the electrolyte, and the heterogeneous element nitrogen on the carbon coating layer can effectively promote the carbon layer to be firmly anchored on the surface of the nickel-rich matrix material, making the carbon coating layer difficult to peel off during a long cycle, thereby further improving its cycle life.

[0012] In the present invention, the gradient reduction of nickel content from the core to the shell and the nitrogen-doped carbon coating layer must cooperate with each other and are indispensable to achieve a precursor with a nickel-rich core and a manganese-rich shell, and the nickel content in the core changes in a gradient concentration, showing a uniform fusion of the core and the shell at the atomic level, solving the problem of structural instability due to composition differences in general core-shell materials, and achieving the unity of high energy density and high safety.

[0013] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0014] Preferably, in the nickel-cobalt-lithium layered oxide core, the molar ratio of nickel to cobalt is (3-18):1, for example, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1 or 18:1, etc., preferably (8-18):1.

[0015] Preferably, in the nickel-cobalt-manganese-lithium layered oxide shell layer, the molar ratio of nickel, cobalt and manganese is (3-18):1:1, for example, 3:1:1, 4:1:1, 5:1:1, 6:1:1, 7:1:1, 8:1:1, 9:1:1, 10:1:1, 11:1:1, 12:1:1, 13:1:1, 14:1:1, 15:1:1, 16:1:1, 17:1:1 or 18:1:1, etc., preferably (8-18):1:1.

[0016] In the present invention, by regulating the molar ratio of nickel to cobalt in the nickel-cobalt-lithium layered oxide core to (3-18):1, and / or regulating the molar ratio of nickel, cobalt and manganese in the nickel-cobalt-manganese-lithium layered oxide shell to (3-18):1:1, the unity of high energy density and high safety can be better achieved.

[0017] Preferably, the thickness of the nitrogen-doped carbon coating layer is 3-10 nm, for example, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm.

[0018] In a second aspect, the present invention provides a method for preparing the nickel-rich layered positive electrode material as described in the first aspect, the preparation method comprising the following steps:

[0019] A nickel salt solution, a cobalt salt solution, a precipitant solution and a complexing agent solution are added in parallel to carry out a first-stage coprecipitation reaction, and then a manganese salt solution is added to continue a second-stage coprecipitation reaction to obtain a positive electrode precursor material;

[0020] The cathode precursor material is mixed with a lithium source and sintered to obtain a nickel-rich matrix material;

[0021] The nickel-rich matrix material is mixed and coated with a nitrogen-doped carbon precursor material, and then carbonized to obtain the nickel-rich layered positive electrode material.

[0022] It should be noted that, in the preparation method provided by the present invention, the coprecipitation reaction in the first stage and the coprecipitation reaction in the second stage are continuous reactions, the only difference being that a manganese salt solution is additionally added in the middle.

[0023] The preparation method provided by the present invention realizes a gradient-decreasing distribution of nickel from the inner core to the shell layer in the preparation stage of the precursor material; thus, after lithium sintering with a lithium source, a nickel-rich matrix material with a core-shell structure is obtained, and a nickel-rich layered positive electrode material with a stable structure and excellent electrochemical performance is obtained by coordinating with a subsequent nitrogen-doped carbon coating layer coating treatment; and the preparation method is simple to operate, does not require a complicated processing process, and is suitable for large-scale production.

[0024] Preferably, during the coprecipitation reaction process of the first stage, the molar ratio of nickel in the nickel salt to cobalt in the cobalt salt is (3-18):1, for example, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1 or 18:1, etc., preferably (8-18):1.

[0025] Preferably, during the coprecipitation reaction process of the second stage, the molar ratio of nickel in the nickel salt, cobalt in the cobalt salt and manganese in the manganese salt is (3-18):1:1, for example, 3:1:1, 4:1:1, 5:1:1, 6:1:1, 7:1:1, 8:1:1, 9:1:1, 10:1:1, 11:1:1, 12:1:1, 13:1:1, 14:1:1, 15:1:1, 16:1:1, 17:1:1 or 18:1:1, etc., preferably (8-18):1:1.

[0026] Preferably, the pH values ​​of the first stage coprecipitation reaction and the second stage coprecipitation reaction are independently 10.5-11.5, for example, 10.5, 10.6, 10.7, 10.8, 10.9, 11, 11.1, 11.2, 11.3, 11.4 or 11.5, etc.

[0027] Preferably, the stirring speeds of the first stage coprecipitation reaction and the second stage coprecipitation reaction are each independently 550-650 rpm, for example, 550 rpm, 560 rpm, 570 rpm, 580 rpm, 590 rpm, 600 rpm, 610 rpm, 620 rpm, 630 rpm, 640 rpm or 650 rpm, etc.

[0028] Preferably, the reaction temperatures of the first-stage coprecipitation reaction and the second-stage coprecipitation reaction are each independently 55-65°C, for example, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C or 65°C, etc.

[0029] Preferably, taking the sum of the reaction times of the first-stage co-precipitation reaction and the second-stage co-precipitation reaction as 1, the reaction time of the first-stage co-precipitation reaction accounts for 1 / 4 to 1 / 3, for example, 1 / 4, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33 or 1 / 3, etc.

[0030] In the present invention, by adjusting the reaction time of the first stage coprecipitation reaction to 1 / 4 to 1 / 3, it is more conducive to the uniform fusion of the core and the shell, and solves the problem of structural instability of general core-shell materials due to composition differences.

[0031] Preferably, the sintering atmosphere includes an oxygen-containing atmosphere.

[0032] It should be noted that the oxygen-containing atmosphere in the present invention is an atmosphere including oxygen, for example, it can be an air atmosphere, a pure oxygen atmosphere, or an oxygen atmosphere.

[0033] Preferably, the sintering includes performing a first sintering and a second sintering in sequence.

[0034] Preferably, the heating rate of the first sintering is 3-5°C / min, such as 3°C / min, 4°C / min or 5°C / min.

[0035] Preferably, the first sintering holding temperature is 480-550°C, for example, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C or 550°C.

[0036] Preferably, the first sintering holding time is 5 to 7 hours, such as 5 hours, 6 hours or 7 hours.

[0037] Preferably, the heating rate of the second sintering is 2-3°C / min, for example, 2°C / min or 3°C / min.

[0038] Preferably, the second sintering holding temperature is 730-810°C, for example, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C or 810°C.

[0039] Preferably, the second sintering holding time is 9 to 13 h, for example, 9 h, 10 h, 11 h, 12 h or 13 h.

[0040] Preferably, the method for preparing the nitrogen-doped carbon precursor material comprises:

[0041] A carbon source, a nitrogen source and a solvent are mixed to obtain a mixed solution, and the mixed solution is subjected to a hydrothermal reaction to obtain a nitrogen-doped carbon precursor material.

[0042] In the present invention, a nitrogen-doped carbon precursor material is first prepared and then coated with a nickel-rich matrix material, which can better achieve the modification of the precursor by chemical coating; compared with directly mixing and coating the carbon source and the nitrogen source with the nickel-rich matrix material, it has the advantage that the carbon layer is firmly anchored on the surface of the nickel-rich NCM positive electrode material.

[0043] Furthermore, the present invention does not impose any special restrictions on the specific types of carbon sources, nitrogen sources and solvents, and those skilled in the art can make adaptive selections and adjustments based on actual needs.

[0044] For example, the carbon source includes but is not limited to at least one of gelatin, pectin or glucose, the nitrogen source includes but is not limited to at least one of melamine, thiourea or urea, and the solvent includes but is not limited to water.

[0045] Preferably, the mass ratio of the carbon source to the nitrogen source is (2-5):1, for example, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1 or 5:1, etc.

[0046] In the present invention, the mass ratio of the carbon source to the nitrogen source is (2-5):1, which further enhances the synergistic effect of the combination of the carbon source and the nitrogen source.

[0047] Preferably, the concentration of the mixed solution is 40-60 g / L, for example, 40 g / L, 45 g / L, 50 g / L, 55 g / L or 60 g / L.

[0048] Preferably, the temperature of the hydrothermal reaction is 120-180°C, for example, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C.

[0049] Preferably, the hydrothermal reaction time is 8 to 12 h, for example, 8 h, 9 h, 10 h, 11 h or 12 h.

[0050] Preferably, the mass ratio of the nickel-rich matrix material to the nitrogen-doped carbon precursor material is (1-3):1, for example, 1:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 2.5:1 or 3:1, etc., preferably (1.5-2):1.

[0051] The present invention limits the mass ratio of the nickel-rich matrix material to the nitrogen-doped carbon precursor material to (1-3):1, which can achieve uniform coating of the nickel-rich matrix material by the nitrogen-doped carbon coating layer, and further adjusts it to (1.5-2):1, which can better play the role of chemical coating in modifying the precursor, thereby improving a series of problems such as large-scale release of lithium ions from subsequent positive electrode materials under high voltage, poor crystal structure stability, and ion mixing.

[0052] Preferably, the carbonization temperature is 700-900°C, for example, 700°C, 725°C, 750°C, 775°C, 800°C, 825°C, 850°C, 875°C or 900°C.

[0053] Preferably, the carbonization time is 1 to 3 hours, such as 1 hour, 2 hours or 3 hours.

[0054] As a preferred technical solution, the preparation method comprises the following steps:

[0055] A nickel salt solution, a cobalt salt solution, a precipitant solution and a complexing agent solution are added in parallel, the molar ratio of nickel in the nickel salt to cobalt in the cobalt salt is (3-18):1, and a first-stage coprecipitation reaction is performed, and then a manganese salt solution is added, the molar ratio of nickel in the nickel salt, cobalt in the cobalt salt and manganese in the manganese salt is (3-18):1:1, and a second-stage coprecipitation reaction is continued to obtain a positive electrode precursor material;

[0056] The cathode precursor material is mixed with a lithium source and sintered to obtain a nickel-rich matrix material;

[0057] The nickel-rich matrix material and the nitrogen-doped carbon precursor material are mixed and coated in a mass ratio of (1.5-2):1, and carbonized at 700-900° C. for 1-3 hours to obtain the nickel-rich layered positive electrode material;

[0058] Wherein, taking the sum of the reaction time of the first stage coprecipitation reaction and the second stage coprecipitation reaction as 1, the reaction time of the first stage coprecipitation reaction accounts for 1 / 4 to 1 / 3;

[0059] The method for preparing the nitrogen-doped carbon precursor material comprises:

[0060] The carbon source, the nitrogen source and the solvent are mixed to obtain a mixed solution with a concentration of 40 to 60 g / L, and a hydrothermal reaction is carried out at 120 to 180° C. for 8 to 12 hours to obtain a nitrogen-doped carbon precursor material.

[0061] It should also be noted that:

[0062] In the preparation method provided by the present invention, except for the above-mentioned characteristic limitations, the specific material types of the remaining raw materials and the preparation process are all conventional technical solutions, and the present invention is applicable to all technical solutions that can be known within a reasonable range by technical personnel in the field.

[0063] Optionally, the salt solutions of the nickel salt, cobalt salt and manganese salt include but are not limited to at least one of nitrate, sulfate, acetate or chloride.

[0064] Optionally, the precipitant includes but is not limited to at least one of sodium hydroxide, potassium hydroxide, sodium carbonate or sodium bicarbonate.

[0065] Optionally, the complexing agent includes but is not limited to at least one of ammonia water, ammonium bicarbonate, ammonium phosphate, ammonium hydrogen phosphate, diammonium hydrogen carbonate, ammonium dihydrogen phosphate, ammonium nitrate, urea or citric acid.

[0066] Optionally, after the second stage co-precipitation reaction is completed, the reaction solution is centrifugally washed and dried in sequence, wherein the centrifugal washing includes first washing with liquid alkali and then washing with water.

[0067] Optionally, the lithium source includes but is not limited to at least one of lithium hydroxide, lithium carbonate, lithium nitrate or lithium acetate; the molar ratio of lithium in the lithium source to the nickel-rich matrix material is (1.01-1.1):1, for example, 1.01:1, 1.02:1, 1.03:1, 1.04:1, 1.05:1, 1.06:1, 1.07:1, 1.08:1, 1.09:1, 1:1 or 1.1:1, etc.

[0068] Optionally, the carbonization atmosphere may be a protective atmosphere, such as a nitrogen atmosphere or an inert gas (such as argon or helium) atmosphere.

[0069] In a third aspect, the present invention further provides a solid-state battery, comprising the nickel-rich layered positive electrode material as described in the first aspect or the nickel-rich layered positive electrode material prepared by the preparation method as described in the second aspect.

[0070] The solid-state battery provided by the present invention comprises a positive electrode plate, a solid electrolyte layer and a negative electrode plate; the nickel-rich layered positive electrode material provided by the present invention is used in the positive electrode plate, and except for the nickel-rich positive electrode material specified in the present invention, the remaining raw materials and preparation processes of the battery are conventional technical solutions, and technical personnel in this field can make adaptive selections and adjustments based on actual needs.

[0071] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0072] Compared with the prior art, the present invention has the following beneficial effects:

[0073] (1) The nickel-rich layered positive electrode material provided by the present invention improves the stability of the positive electrode material during the cycle process by virtue of the gradient reduction of the nickel content from the inner core to the shell layer and the synergistic cooperation of the nitrogen-doped carbon coating layer; at the same time, the carbon coating layer can further enhance the electronic and ionic conductivity and more effectively avoid direct contact and reaction between the active material and the electrolyte. The heterogeneous elemental nitrogen on the carbon coating layer can effectively promote the carbon layer to be firmly anchored on the surface of the nickel-rich matrix material, making it difficult for the carbon coating layer to be peeled off during a long cycle, thereby further improving its cycle life.

[0074] (2) The preparation method provided by the present invention realizes a gradient distribution of nickel from the inner core to the shell layer during the preparation stage of the precursor material; thus, after sintering with a lithium source, a nickel-rich matrix material with a core-shell structure is obtained, and a nickel-rich layered positive electrode material with a stable structure and excellent electrochemical properties is obtained by the subsequent coating treatment of a nitrogen-doped carbon coating layer; and the preparation method is simple to operate, does not require a complicated processing process, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] Figure 1 This is a SEM image of the positive electrode precursor material provided in Example 1 of the present invention.

[0076] Figure 2 The SEM image and EDS image of the cross section of the positive electrode precursor material provided in Example 1 of the present invention.

[0077] Figure 3 This is a SEM image of the nickel-rich layered positive electrode material provided in Example 1 of the present invention.

[0078] Figure 4 This is a TEM image of the nickel-rich layered positive electrode material provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0079] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0080] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.

[0081] In the description of this application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0082] Example 1

[0083] This embodiment provides a nickel-rich layered positive electrode material, the nickel-rich layered positive electrode material comprising a nickel-rich base material and a nitrogen-doped carbon coating layer coated on the surface of the nickel-rich base material;

[0084] The nickel-rich matrix material includes a nickel-cobalt-lithium layered oxide core (the molar ratio of Ni:Co is 8:1) and a nickel-cobalt-manganese-lithium layered oxide shell layer (the molar ratio of Ni:Co:Mn is 8:1:1) located on the surface of the nickel-cobalt core; the thickness of the nitrogen-doped carbon coating layer is 5nm.

[0085] The preparation method of the nickel-rich layered positive electrode material is as follows:

[0086] S1: NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O are prepared into nickel sulfate, cobalt sulfate, and manganese sulfate solutions of the same volume of 0.7L, wherein the molar concentration ratio of nickel sulfate, cobalt sulfate, and manganese sulfate solutions is 8:1:1, and then the prepared nickel sulfate and cobalt sulfate solutions and 1L of NaOH with a molar concentration of 8mol / L and 2L of NH3·H2O solution with a molar concentration of 2mol / L are slowly added into the coprecipitation reactor to carry out the first stage of coprecipitation reaction. After reacting for 5h, the manganese sulfate solution is slowly added to carry out the second stage of coprecipitation reaction. The reaction time of the whole coprecipitation reaction is 20h. During the reaction, the rotation speed is maintained at 600rpm, the temperature is maintained at 60°C, and the pH is 10.8. After the reaction is completed, the obtained solution is centrifuged and washed 3 times with a 3% mass fraction NaOH solution and an aqueous solution, and then the obtained precipitate is dried at 60°C to obtain a positive electrode precursor material;

[0087] S2: The cathode precursor material and LiOH·H2O powder were uniformly mixed at a molar ratio of 1:1.05, and then the first sintering was performed at 520°C at 3°C / min in an oxygen atmosphere, and the temperature was kept for 6 hours; the second sintering was performed at 780°C at 3°C / min, and the temperature was kept for 10 hours. After the sintering was completed, the material was cooled to room temperature to obtain a nickel-rich matrix material;

[0088] S3: preparing a 50 g / L aqueous solution of gelatin and melamine in a mass ratio of 3:1, subjecting the mixture to a hydrothermal reaction at 150° C. for 10 h, and filtering and drying the mixture to obtain a nitrogen-doped carbon precursor material;

[0089] S4: The nickel-rich matrix material and the nitrogen-doped carbon precursor material are uniformly mixed in a mass ratio of 2:1, placed in a nitrogen atmosphere, and carbonized at 800° C. for 2 h to finally obtain the nickel-rich layered positive electrode material.

[0090] Figure 1 The SEM image of the positive electrode precursor material provided in Example 1 of the present invention is shown. Figure 1 It can be seen that the positive electrode precursor material obtained in Example 1 has a spherical morphology.

[0091] Figure 2 The SEM image and EDS image of the cross section of the positive electrode precursor material provided in Example 1 of the present invention are shown. Figure 2 It can be seen that the Ni concentration of the positive electrode precursor material obtained in Example 1 is higher near the core and lower near the surface area; at the same time, the Mn concentration gradually increases from the middle to the outer surface, indicating that the synthesis of the gradient structure is successful.

[0092] Figure 3 The SEM image of the nickel-rich layered positive electrode material provided in Example 1 of the present invention is shown. Figure 3 It can be seen that the nickel-rich positive electrode material obtained in Example 1 retains the spherical morphology and has obvious attachments on the surface, which proves the successful coating of the nitrogen-doped carbon coating layer.

[0093] Figure 4 The TEM image of the nickel-rich layered positive electrode material provided in Example 1 of the present invention is shown. Figure 4 It can be seen that the surface of the nickel-rich layered positive electrode material provided in Example 1 has an obvious carbon coating layer, which further proves the successful coating of nitrogen-doped carbon.

[0094] Example 2

[0095] This embodiment provides a nickel-rich layered positive electrode material, the nickel-rich layered positive electrode material comprising a nickel-rich base material and a nitrogen-doped carbon coating layer coated on the surface of the nickel-rich base material;

[0096] The nickel-rich matrix material includes a nickel-cobalt-lithium layered oxide core (the molar ratio of Ni:Co is 8:1) and a nickel-cobalt-manganese-lithium layered oxide shell layer (the molar ratio of Ni:Co:Mn is 8:1:1) located on the surface of the nickel-cobalt core; the thickness of the nitrogen-doped carbon coating layer is 7nm.

[0097] The preparation method of the nickel-rich layered positive electrode material is as follows:

[0098] S1: NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O are prepared into nickel sulfate, cobalt sulfate, and manganese sulfate solutions of the same volume of 0.7L, wherein the molar concentration ratio of nickel sulfate, cobalt sulfate, and manganese sulfate solutions is 8:1:1, and then the prepared nickel sulfate and cobalt sulfate solutions and 1L of NaOH with a molar concentration of 8mol / L and 2L of NH3·H2O solution with a molar concentration of 2mol / L are slowly added into the coprecipitation reactor to carry out the first stage of coprecipitation reaction. After the reaction for 6h, the manganese sulfate solution is slowly added to carry out the second stage of coprecipitation reaction. The reaction time of the entire coprecipitation reaction is 18h. During the reaction, the rotation speed is maintained at 550rpm, the temperature is maintained at 55°C, and the pH is 11.5. After the reaction is completed, the obtained solution is centrifuged and washed 5 times with a 3% mass fraction NaOH solution and an aqueous solution, and then the obtained precipitate is dried at 60°C to obtain a positive electrode precursor material;

[0099] S2: The cathode precursor material and LiOH·H2O powder were uniformly mixed at a molar ratio of 1:1.05, and then the first sintering was performed at 480°C at 5°C / min in an oxygen atmosphere, and the temperature was kept for 7 hours; the second sintering was performed at 730°C at 2°C / min, and the temperature was kept for 13 hours. After the sintering was completed, the material was cooled to room temperature to obtain a nickel-rich matrix material;

[0100] S3: preparing a 40 g / L aqueous solution of gelatin and melamine in a mass ratio of 5:1, subjecting the mixture to a hydrothermal reaction at 120° C. for 12 h, and filtering and drying the mixture to obtain a nitrogen-doped carbon precursor material;

[0101] S4: The nickel-rich matrix material and the nitrogen-doped carbon precursor material are uniformly mixed in a mass ratio of 1.5:1, placed in a nitrogen atmosphere, and carbonized at 900° C. for 1 hour to finally obtain the nickel-rich layered positive electrode material.

[0102] Example 3

[0103] This embodiment provides a nickel-rich layered positive electrode material, the nickel-rich layered positive electrode material comprising a nickel-rich base material and a nitrogen-doped carbon coating layer coated on the surface of the nickel-rich base material;

[0104] The nickel-rich matrix material includes a nickel-cobalt-lithium layered oxide core (the molar ratio of Ni:Co is 8:1) and a nickel-cobalt-manganese-lithium layered oxide shell layer (the molar ratio of Ni:Co:Mn is 8:1:1) located on the surface of the nickel-cobalt core; the thickness of the nitrogen-doped carbon coating layer is 4nm.

[0105] The preparation method of the nickel-rich layered positive electrode material is as follows:

[0106] S1: NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O are prepared into nickel sulfate, cobalt sulfate, and manganese sulfate solutions of the same volume of 0.7L, wherein the molar concentration ratio of nickel sulfate, cobalt sulfate, and manganese sulfate solutions is 8:1:1, and then the prepared nickel sulfate and cobalt sulfate solutions and 1L of NaOH with a molar concentration of 8mol / L and 2L of NH3·H2O solution with a molar concentration of 2mol / L are slowly added into the coprecipitation reactor to carry out the first stage of coprecipitation reaction. After the reaction for 6h, the manganese sulfate solution is slowly added to carry out the second stage of coprecipitation reaction. The reaction time of the entire coprecipitation reaction is 20h. During the reaction, the rotation speed is maintained at 650rpm, the temperature is maintained at 65°C, and the pH is 10.5. After the reaction is completed, the obtained solution is centrifuged and washed 3 times with a 3.5% mass fraction NaOH solution and an aqueous solution, and then the obtained precipitate is dried at 60°C to obtain a positive electrode precursor material;

[0107] S2: The cathode precursor material and LiOH·H2O powder were uniformly mixed at a molar ratio of 1:1.05, and then the temperature was raised to 550°C at 3°C / min in an oxygen atmosphere for the first sintering, and the temperature was kept for 5 hours; then the temperature was raised to 810°C at 3°C / min for the second sintering, and the temperature was kept for 9 hours. After the sintering was completed, it was cooled to room temperature to obtain a nickel-rich matrix material;

[0108] S3: preparing a 40 g / L aqueous solution of gelatin and melamine in a mass ratio of 2:1, subjecting the mixture to a hydrothermal reaction at 180° C. for 8 h, and obtaining a nitrogen-doped carbon precursor material after filtering and drying;

[0109] S4: The nickel-rich matrix material and the nitrogen-doped carbon precursor material are uniformly mixed in a mass ratio of 2.3:1, placed in a nitrogen atmosphere, and carbonized at 700° C. for 3 hours to finally obtain the nickel-rich layered positive electrode material.

[0110] Example 4

[0111] The difference between this embodiment and Embodiment 1 is that in this embodiment, the nickel-rich matrix material includes a nickel-cobalt-lithium layered oxide core (the molar ratio of Ni:Co is 18:1) and a nickel-cobalt-manganese-lithium layered oxide shell (the molar ratio of Ni:Co:Mn is 18:1:1) located on the surface of the nickel-cobalt core.

[0112] In S1 of the preparation method, NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O are prepared into nickel sulfate, cobalt sulfate, and manganese sulfate solutions with the same volume of 0.7 L, wherein the molar concentration ratio of the nickel sulfate, cobalt sulfate, and manganese sulfate solutions is 18:1:1.

[0113] The rest of the preparation methods and parameters were the same as those in Example 1.

[0114] Example 5

[0115] The difference between this embodiment and embodiment 1 is that in step S3 of this embodiment, the nitrogen source is thiourea instead of melamine.

[0116] The rest of the preparation methods and parameters were the same as those in Example 1.

[0117] Example 6

[0118] The difference between this embodiment and embodiment 1 is that in step S3 of this embodiment, the mass ratio of gelatin to melamine is 1:1.

[0119] The rest of the preparation methods and parameters were the same as those in Example 1.

[0120] Example 7

[0121] The difference between this embodiment and embodiment 1 is that the mass ratio of gelatin to melamine in step S3 of this embodiment is 6:1.

[0122] The rest of the preparation methods and parameters were the same as those in Example 1.

[0123] Example 8

[0124] The difference between this embodiment and embodiment 1 is that in step S3 of this embodiment, the temperature of the hydrothermal reaction is 100°C.

[0125] The rest of the preparation methods and parameters were the same as those in Example 1.

[0126] Example 9

[0127] The difference between this embodiment and embodiment 1 is that in step S3 of this embodiment, the temperature of the hydrothermal reaction is 200°C.

[0128] The rest of the preparation methods and parameters were the same as those in Example 1.

[0129] Example 10

[0130] The difference between this embodiment and embodiment 1 is that in step S3 of this embodiment, no hydrothermal reaction is performed, and the mixed solution is directly dried before performing S4.

[0131] The rest of the preparation methods and parameters were the same as those in Example 1.

[0132] Embodiment 11

[0133] The difference between this embodiment and embodiment 1 is that in step S4 of this embodiment, the nickel-rich matrix material and the nitrogen-doped carbon precursor material are uniformly mixed in a mass ratio of 3:1.

[0134] The rest of the preparation methods and parameters were the same as those in Example 1.

[0135] Example 12

[0136] The difference between this embodiment and embodiment 1 is that in step S4 of this embodiment, the nickel-rich matrix material and the nitrogen-doped carbon precursor material are uniformly mixed in a mass ratio of 1:1.

[0137] The rest of the preparation methods and parameters were the same as those in Example 1.

[0138] Comparative Example 1

[0139] The difference between this comparative example and Example 1 is that the nickel-rich matrix material of this example is nickel-cobalt-manganese-lithium layered oxide, that is, a pure shell material.

[0140] In step S1 of the preparation method, the prepared nickel sulfate, cobalt sulfate solution and manganese sulfate solution are added together from the beginning of the coprecipitation reaction, that is, manganese sulfate is not added in stages.

[0141] The rest of the preparation methods and parameters were the same as those in Example 1.

[0142] Comparative Example 2

[0143] The difference between this comparative example and Example 1 is that the nickel-rich layered positive electrode material in this example does not contain a nitrogen-doped carbon coating layer.

[0144] In the preparation method, steps S3 and S4 are not performed.

[0145] The rest of the preparation methods and parameters were the same as those in Example 1.

[0146] Comparative Example 3

[0147] The difference between this comparative example and comparative example 1 is that the nickel-rich layered positive electrode material in this comparative example does not contain a nitrogen-doped carbon coating layer.

[0148] In the preparation method, steps S3 and S4 are not performed.

[0149] The rest of the preparation methods and parameters were the same as those in Comparative Example 1.

[0150] Batteries were prepared and performance tested using the nickel-rich layered positive electrode materials provided in Examples 1-12 and Comparative Examples 1-3.

[0151] Battery preparation:

[0152] First, the nickel-rich positive electrode material provided in the embodiment and the comparative example and the solid electrolyte LPSCI (Li 5.5 PS 4.5 Cl 1.5 ), vapor grown carbon fiber (VGCF) are uniformly mixed in a mass ratio of 60:37:3 to obtain a composite positive electrode material; then, 20 mg of the composite positive electrode material is evenly placed in a tableting mold with a diameter of 10 mm, pressed flat, and 120 mg of LPSCI is added to tablet at a pressure of 500 MPa. The process lasts for 2 min. After tableting, 20 mg of the composite negative electrode material (Li metal: LPSCI: acetylene black = 60:36:4) is added to tablet again to obtain a three-layer solid sheet, and the solid sheet is placed in a stainless steel solid-state battery mold and sealed as a complete all-solid-state battery.

[0153] Performance test: The assembled all-solid-state battery was subjected to constant current charge and discharge test. The test conditions were 25°C and the test range was 1.3-2.8V, i.e. 2.85-4.35V (vs. Li / Li+). The test process was to first cycle for 5 times at a current density of 0.1C, then cycle for 5 times at 0.3C, 0.5C, 1C, 2C, 5C, and 0.1C respectively, and finally perform a long cycle test for 200 cycles at 0.2C. The test results are shown in Table 1.

[0154] Table 1

[0155]

[0156] In summary, the nickel-rich layered positive electrode material provided by the present invention improves the stability of the positive electrode material during the cycle process through the gradient reduction of the nickel content from the inner core to the shell layer and the synergistic cooperation of the nitrogen-doped carbon coating layer; at the same time, the carbon coating layer can further enhance the electronic and ionic conductivity, and more effectively avoid direct contact and reaction between the active material and the electrolyte, and the heterogeneous elemental nitrogen on the carbon coating layer can effectively promote the carbon layer to be firmly anchored on the surface of the nickel-rich matrix material, making the carbon coating layer difficult to peel off during a long cycle, thereby further improving its cycle life.

[0157] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A nickel-rich layered positive electrode material, characterized in that: The nickel-rich layered positive electrode material comprises a nickel-rich base material and a nitrogen-doped carbon coating layer coated on the surface of the nickel-rich base material; The nickel-rich matrix material includes a nickel-cobalt-lithium layered oxide core and a nickel-cobalt-manganese-lithium layered oxide shell located on the surface of the nickel-cobalt-lithium layered oxide core; the molar ratio of nickel in the nickel-cobalt-lithium layered oxide core is greater than the molar ratio of nickel in the nickel-cobalt-manganese-lithium layered oxide shell.

2. The nickel-rich layered positive electrode material according to claim 1, characterized in that: In the nickel-cobalt-lithium layered oxide core, the molar ratio of nickel to cobalt is (3-18):1, preferably (8-18):1; Preferably, in the nickel-cobalt-manganese-lithium layered oxide shell layer, the molar ratio of nickel, cobalt and manganese is (3-18):1:1, preferably (8-18):1:1; Preferably, the thickness of the nitrogen-doped carbon coating layer is 3-10 nm.

3. A method for preparing a nickel-rich layered positive electrode material as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: A nickel salt solution, a cobalt salt solution, a precipitant solution and a complexing agent solution are added in parallel to carry out a first-stage coprecipitation reaction, and then a manganese salt solution is added to continue a second-stage coprecipitation reaction to obtain a positive electrode precursor material; The cathode precursor material is mixed with a lithium source and sintered to obtain a nickel-rich matrix material; The nickel-rich matrix material is mixed and coated with a nitrogen-doped carbon precursor material, and then carbonized to obtain the nickel-rich layered positive electrode material.

4. The preparation method according to claim 3, characterized in that: During the coprecipitation reaction in the first stage, the molar ratio of nickel in the nickel salt to cobalt in the cobalt salt is (3-18):1, preferably (8-18):1; Preferably, during the coprecipitation reaction in the second stage, the molar ratio of nickel in the nickel salt, cobalt in the cobalt salt and manganese in the manganese salt is (3-18):1:1, preferably (8-18):1:1; Preferably, the pH values ​​of the first stage coprecipitation reaction and the second stage coprecipitation reaction are independently 10.5 to 11.5; Preferably, the stirring speed of the first stage coprecipitation reaction and the second stage coprecipitation reaction is independently 550-650 rpm; Preferably, the reaction temperature of the first stage coprecipitation reaction and the second stage coprecipitation reaction is independently 55 to 65°C; Preferably, taking the sum of the reaction times of the first-stage co-precipitation reaction and the second-stage co-precipitation reaction as 1, the reaction time of the first-stage co-precipitation reaction accounts for 1 / 4 to 1 / 3.

5. The preparation method according to claim 3 or 4, characterized in that: The sintering atmosphere includes an oxygen-containing atmosphere; Preferably, the sintering includes sequentially performing a first sintering and a second sintering; Preferably, the heating rate of the first sintering is 3-5°C / min, the holding temperature of the first sintering is 480-550°C, and the holding time of the first sintering is 5-7h; Preferably, the heating rate of the second sintering is 2-3° C. / min, the holding temperature of the second sintering is 730-810° C., and the holding time of the second sintering is 9-13 h.

6. The preparation method according to any one of claims 3 to 5, characterized in that: The method for preparing the nitrogen-doped carbon precursor material comprises: A carbon source, a nitrogen source and a solvent are mixed to obtain a mixed solution, and the mixed solution is subjected to a hydrothermal reaction to obtain a nitrogen-doped carbon precursor material.

7. The preparation method according to claim 6, characterized in that: The mass ratio of the carbon source to the nitrogen source is (2-5):1; Preferably, the concentration of the mixed solution is 40-60 g / L; Preferably, the temperature of the hydrothermal reaction is 120-180° C., and the time of the hydrothermal reaction is 8-12 hours.

8. The preparation method according to any one of claims 3 to 7, characterized in that: The mass ratio of the nickel-rich matrix material to the nitrogen-doped carbon precursor material is (1-3):1, preferably (1.5-2):1; Preferably, the carbonization temperature is 700-900° C., and the carbonization time is 1-3 hours.

9. The preparation method according to claim 3, characterized in that: The preparation method comprises the following steps: A nickel salt solution, a cobalt salt solution, a precipitant solution and a complexing agent solution are added in parallel, the molar ratio of nickel in the nickel salt to cobalt in the cobalt salt is (3-18):1, and a first-stage coprecipitation reaction is performed, and then a manganese salt solution is added, the molar ratio of nickel in the nickel salt, cobalt in the cobalt salt and manganese in the manganese salt is (3-18):1:1, and a second-stage coprecipitation reaction is continued to obtain a positive electrode precursor material; The cathode precursor material is mixed with a lithium source and sintered to obtain a nickel-rich matrix material; The nickel-rich matrix material and the nitrogen-doped carbon precursor material are mixed and coated in a mass ratio of (1.5-2):1, and carbonized at 700-900° C. for 1-3 hours to obtain the nickel-rich layered positive electrode material; Wherein, taking the sum of the reaction time of the first stage coprecipitation reaction and the second stage coprecipitation reaction as 1, the reaction time of the first stage coprecipitation reaction accounts for 1 / 4 to 1 / 3; The method for preparing the nitrogen-doped carbon precursor material comprises: The carbon source, the nitrogen source and the solvent are mixed to obtain a mixed solution with a concentration of 40 to 60 g / L, and a hydrothermal reaction is carried out at 120 to 180° C. for 8 to 12 hours to obtain a nitrogen-doped carbon precursor material.

10. A solid-state battery, characterized in that: The solid-state battery comprises the nickel-rich layered positive electrode material as described in claim 1 or 2 or the nickel-rich layered positive electrode material prepared by the preparation method as described in any one of claims 3-9.

Citation Information

Cited By

  • Ultrahigh-nickel single-crystal positive electrode material, preparation method and positive electrode

    CN121609376A